Mechanism of Ru(III) Catalysis in Oxidation of Levulinic Acid by Acidic Solution of N-Bromobenzamide - Kumari Pandey, Shanti; Yadav, S.P.S.; Prasad, Manju; Prasad, Janak (Asian Journal of Chemistry, 2010)
Kinetic data observed in Ru(III) catalysed oxidation of levulinic acid (LA) by N-bromobenzamide (NBB) in perchloric acid in the presence of mercuric acetate as Br- scavenger have been reported. The reaction shows first order at low [NBB] but zero order in higher concentration range of NBB. First order in Ru(III) and zero order in LA were observed. Positive effect of [H+] and negative effect of addition of sodium perchlorate, potassium chloride and benzamide was observed. A suitable mechanism in conformity with the observed kinetics has been proposed.